Exploring In Vitro and Ex Vivo Models as Pharmacological Tool for Acute Lung Injury - Sadhu, Piyushkumar (Asian Journal of Pharmaceutics (AJP), 2025)
Acute lung injury (ALI) remains a formidable clinical challenge, compounded by the scarcity of effective therapeutic options. Preclinical studies are crucial for evaluating the safety and efficacy of new drugs and formulations before clinical trials. Conventionally, animal models have been widely used for ALI research, but ethical concerns and differences from human physiology limit their effectiveness. This state-of-the-art review provides a comprehensive overview of in vitro and ex vivo models over traditional animal studies in ALI studies. While these models cannot entirely replace animal studies, they offer the potential to reduce the number of animal trials and improve drug efficacy and safety. Bridging the gap between in vitro studies and in vivo animal models, they address ethical concerns and provide more accurate data for human applications. Specifically, their application in ALI research highlights their potential in developing novel therapeutic approaches. However, challenges, such as maintaining tissue viability and replicating the complexity of human lungs still exist. Future advancements in bioengineering and personalized medicine promise to enhance these models’ relevance, paving the way for more effective ALI therapies.